다차원 데이터 큐브 모델을 이용한 구제역의 위기 대응 방안 분석 - 노병준(Byeongjoon Noh); 이종욱(Jonguk Lee); 박대희(Daihee Park); 정용화(Yongwha Chung) (한국콘텐츠학회 논문지, 17(5), 2017)
The ex-post evaluation of governmental crisis management is an important issues since it is necessary to prepare for the future disasters and becomes the cornerstone of our success as well. In this paper, we propose a data cube model with data mining techniques for the analysis of governmental crisis management strategies and ripple effects of foot-and-mouth(FMD) disease using the online news articles. Based on the construction of the data cube model, a multidimensional FMD analysis is performed using on line analytical processing operations (OLAP) to assess the temporal perspectives of the spread of the disease with varying levels of abstraction. Furthermore, the proposed analysis model provides useful information that generates the causal relationship between crisis response actions and its social ripple effects of FMD outbreaks by applying association rule mining. We confirmed the feasibility and applicability of the proposed FMD analysis model by implementing and applying an analysis system to FMD outbreaks from July 2010 to December 2011 in South Korea. 재난 재해 발생 시, 정부의 위기 대응방식에 대한 사후 평가는 향후 유사한 위기 상황이 발생할 경우를 대비하고 국가의 장기적인 위기관리의 초석이 되는 필수적인 단계이다. 본 논문에서는 국내에서 발생한 구제역에 관하여 정부에서 어떠한 대응 전략을 펼쳤는지를 언론에 보도된 기사 내용을 통해 분석한 연구로써, 먼저 온라인 뉴스 기사로부터 구제역에 관한 키워드들을 추출하여 데이터 큐브를 구성한 후, OLAP 연산과 연관규칙 분석을 수행함으로써 시간 축에 따른 정부의 위기상황 대응행동 및 그에 따른 사회적 파급 효과들을 분석한다. 구제역이 가장 심각했던 2010년 11월부터 2011년 12월까지 국내에서 발생한 구제역에 관한 정부의 위기 상황 대응 방법을 사례분석을 통해 분석하였다.